Measurement of directional range components of nuclear recoil tracks in a fiducialised dark matter detector. (18th October 2017) - Battat, J.B.R.; Daw, E.J.; Ezeribe, A.C.; Gauvreau, J.-L.; Harton, J.L.; Lafler, R.; Lee, E.R.; Loomba, D.; Lynch, W.; Miller, E.H.; Mouton, F.; Paling, S.; et al.
Abstract: We present results from the first measurement of axial range components of fiducialized neutron induced nuclear recoil tracks using the DRIFT directional dark matter detector. Nuclear recoil events are fiducialized in the DRIFT experiment using temporal charge carrier separations between different species of anions in 30:10:1 Torr of CS_2 2 :CF_4 4 :O_2 2 gas mixture. For this measurement, neutron-induced nuclear recoil tracks were generated by exposing the detector to^{252} 252 Cf source from different directions. Using these events, the sensitivity of the detector to the expected axial directional signatures were investigated as the neutron source was moved from one detector axis to another. Results obtained from these measurements show clear sensitivity of the DRIFT detector to the axial directional signatures in this fiducialization gas mode.